Nuclear Multi‐Microsatellite Marker Profiling Provides Clues to Molecular Genetic Diversity in Culture‐Based Caspian Beluga Sturgeon (Huso huso) Brood Stocks: Ecological Mirror for Restoration - Mehdi Moghim; Arash Javanmard; Faramarz Lolaei; Mohammad‐Javad Taghavi; Shima Bakhshalizadeh (Veterinary Medicine and Science)
ABSTRACT The decreasing natural genetic diversity within intense beluga sturgeon aquaculture presents a complex challenge for culture‐based sturgeon stocks. The present report aims to assess the situation by utilizing advanced capillary electrophoresis (CE) and multi‐microsatellite nuclear marker tools. We conducted a study involving 436 individuals of both sexes, collected from eight breeder private farms with diverse breeding histories and generational backgrounds. Through the application of eight microsatellites, we amplified a non‐coding core genomic region in the species, followed by CE to provide double confirmation of observed genotype and actual allelic size SSR profiling. Utilizing molecular descriptive statistics in the POPGENE software, we calculated allele frequencies, expected and observed heterozygosity within populations, the number of observed and effective alleles (na and ne) and the Shannon's Information Index. Furthermore, we performed molecular analysis of variance (AMOVA), model‐based clustering, principal coordinate analysis (PCoA) and STRUCTURE analysis to genetically characterize the populations. It was revealed that LS19 (na = 16) and Afu54 (na = 3) exhibited the highest and lowest levels of polymorphisms, respectively, within the studied families. Moreover, the Iranian Fisheries Research Organization (IFRO) farm population was found to have the highest genetic diversity (Ave_Het = 0.67), whereas the Rajaeei Sturgeon Private Farm (RJI) displayed the lowest diversity score (Ave_Het = 0.55) among the examined populations. INS and Jahanpouri Sturgeon Private Farm (JPR) showed the highest similarity (0.91), whereas the Saeei Sturgeon Private Farm had the lowest genetic distance, with a similarity score of 0.74 among the populations studied. Furthermore, the evidence from the STRUCTURE analysis highlighted notable levels of allelic sharing and admixture among the eight studied populations, indirectly indicating the presence of genetic diversity within each population and the relatively low genetic distance between the populations. The results demonstrate a significant level of genetic variability, providing evidence that supports the low value of inbreeding in brood management.